Upaya Meningkatkan Hasil Belajar Siswa Kelas X-MIPA-2 Melalui Metode Observasi Yang Divariasikan dengan LKS Word Square pada Materi Klasifikasi Hewan di SMAN 1 Bluto Tahun Pelajaran 2018-2019 - Yushien Chairanie (Tafhim Al-'Ilmi, 2022)
Abstract Based on the observations of class X-MIPA-2 SMAN 1 Bluto, most of the learning atmosphere is still monotonous and student activity is lacking. For that we need an effort that can increase the effectiveness of student learning. This research was conducted in class X-MIPA-2 because the characteristics of learning outcomes in Animal Classification materials are still low. Efforts to improve the quality of learning are through various methods and according to the material. This research was designed through Classroom Action Research (CAR). The purpose of this study was to determine the increase in learning outcomes of Animal Classification material through the application of the observation method which was varied with Wordsquare worksheets in class X-MIPA-2 SMAN 1 Bluto. The subject of this research is class X-MIPA-2 SMAN 1 Bluto with 40 students. This research was conducted in two cycles. Each cycle consists of 4 stages, namely: planning (planning), implementation (acting), observation (observing), and reflection (reflecting). The indicators of the success of this research are (1) an increase in the percentage of students who get a score of 65 or the number of students who study thoroughly increases to 85%, (2) completeness of classical activities 75%. Based on the results of the study, it was obtained that the percentage increase in the achievement of classical learning mastery in the first cycle was 77.5% and the second cycle was 87.5%, while the classical activity in the first cycle was 61.25% and the second cycle was 76.25%. The conclusion of this study is that through the application of the observation method that is varied with the Wordsquare worksheet on the Animal Classification material, it can improve student learning outcomes in class X-MIPA-2. Meanwhile, the suggestion of this research is that the observation method that is varied with the Wordsquare worksheet needs to be applied to other biological materials because the observation method that is varied with the Wordsquare worksheet makes it easier for students to understand the material being studied. Kata kunci: Hasil Belajar, Metode Observasi Variasi LKS Word Square, Materi Klasifikasi Hewan